Analisis Implementasi Akuntansi Manajemen 4.0: Studi pada Pabrik Gula Madukismo - Ngaisaroh, Nofita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The industrial world that is growing to the era of the industrial revolution 4.0 made the industry switch to the integration of storage system machines and manufacturing operations in the form of cyber-physical production systems (CPPS) to the concept of smart factory. The development of this industrial environment directly impacts the application of corporate management accounting practices. The IFAC management accounting practice model classifies the transformation of management accounting practices from traditional to contemporary. Research on management accounting practices in the manufacturing industry in the industrial era 4.0 is still minimal, especially in the sugar industry which plays a role to meet the needs of the general public. This study uses qualitative methods using primary data through questionnaires and interviews and secondary data from previous research and company documents. Based on the results of the analysis conducted, the conclusion obtained that PG Madukismo is still widely applying traditional management accounting practices even though several contemporary management accounting practices have been applied. PG Madukismo has just applied industrial processes at the industrial stage 2.0, specifically related to production with the help of electrical energy and prioritizes the labor-intensive spirit of its business processes.